Analiza i ocena skutków wprowadzenia motu proprio Mitis Iudex Dominus Iesus w zakresie określania właściwości miejscowej - Poczmański, Michał (Ius Matrimoniale, 2017)
The amendments caused by motu proprio Mitis Iudex Dominus Iesus are currently broadly discussed, court’s employees are trying to cope with it and they are doing their best it in order to implement the new regulations and adapt them to their everyday work. The analysis and considerations within the article aim at presenting the changes made in those regulations. The author focuses on how the defining of local jurisdiction of courts entitled to adjudicate in particular case, has been broadened. The potential dangers and risks that may arise due to the amendments have been defined and presented on the basis of analysis of the regulations from over last hundred years. Those risks are relevant both in the context of searching for the Truth as well as smooth operating of Church courts. The main source of those risks is people’s (petitioners’) attitude, not serious enough and superficial, toward the case of invalidity of the marriage. The author enumerates that their priority is to finalize the case quickly and efficiently as well as to minimalize the court costs. In the author’s opinion the foresight is needed in order to prevent and counteract the effects of this kind of malpractices.